Methodological Synthesis in Quantitative L2 Research: A Review of Reviews and a Case Study of Exploratory Factor Analysis. Issue 1 (June 2015) - Plonsky, Luke; Gonulal, Talip; Norris, John M.; Ross, Steven J.; Schoonen, Rob
<x xml:space="preserve">Abstract</x> Research synthesis and meta‐analysis provide a pathway to bring together findings in a given domain with greater systematicity, objectivity, and transparency than traditional reviews. The same techniques and corresponding benefits can be and have been applied to examine methodological practices in second language (L2) research (e.g., Plonsky, 2013). In the first half of this paper, we integrate findings, trends, and critiques from a number of syntheses to both illustrate the potential of this approach and to promote more methodologically informed research practices. Our emphasis here is on study designs and sampling practices. In the second half, we provide an example of a methodological synthesis that reviews the use of one particular statistical technique as applied in L2 research: exploratory factor analysis (EFA). Here and throughout the chapter, we provide specific recommendations for primary research as well as for future efforts to synthesize methodological practices in the field.